Dr. Benjamin Rush (1746-1813) and the Judaeo-Christian Origins of American Education - Donald J. D'Elia (Educational Considerations, 1992)
Dr. Benjamin Rush, America's leading physician and signer of the Declaration of Independence, was probably the most articulate and comprehensive spokesman for the true meaning of the American Revolution.